PENGARUH KOMPENSASI DAN GAYA KEPEMIMPINANTERHADAP KINERJA KARYAWAN RUMAH SAKIT UTAMA HUSADA AMBULU JEMBER - Said Mardijanto (Jurnal Riset Manajemen dan Bisnis, 2015)
h: 0px; "> This study aimed to examine the effect compensation and leadership style on employee’s performanceof Utama Husada Hospital Ambulu Jember. Respondents used in this study are employees of UtamaHusada Hospital Ambulu Jember as many as 45 employees. Respondents selected by random method.Collecting data using instruments such as questionnaires and tested the validity and reliability test.Analysis of data using multiple regression. The results showed that compensation and leadership styleinfluence on employee’s performance. Other results of the study indicate that leadership style has adominant influence on employee’s performance when compared with the compensation. This resultimplies that the compensation and leadership style has a significant influence on employee’sperformance of Utama Husada Hospital.Keywords : Compensation, Leadership Style, Employee’s Performance